Governing the Sustainable Development Goals Quantification in Global Public Policy - Bandola-Gill, Justyna; Grek, Sotiria; Tichenor, Marlee (Sustainable Development Goals Series, 2022)
XVII, 165 p. 9 illus., 8 illus. in color.